2012
DOI: 10.1038/jhh.2012.38
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic training-induced improvements in arterial stiffness are not sustained in older adults with multiple cardiovascular risk factors

Abstract: There is a well-established relationship between increased arterial stiffness and cardiovascular mortality. We examined whether a long-term aerobic exercise intervention (6 months) would increase arterial compliance in older adults with hypertension complicated by Type 2 diabetes (T2DM) and hyperlipidemia. A total of 52 older adults (mean age 69.3±0.6 years, 30 males and 22 females) with diet/oral hypoglycemic-controlled T2DM, hypertension and hypercholesterolemia were recruited. Subjects were randomly assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 35 publications
3
22
0
6
Order By: Relevance
“…b, brachial; c, central; SBP, systolic blood pressure; DBP, diastolic blood pressure; PP, pulse pressure; MAP, mean arterial pressure; P1 H, aortic incident pressure wave; AP, aortic augmentation pressure; AGI, aortic augmentation index; AGI@75HR, aortic augmentation adjusted for heart rate; HR, heart rate; SEVR, subendocardial viability ratio; TTI, tension time index; DTI, diastolic time index; AoTr, return of aortic reflective wave; cfPWV, carotid-femoral pulse wave velocity (PWV); crPWV, carotid-redial PWV; Dc, carotid diameter in diastole; CSA, cross-sectional area; CCA, common carotid artery; W/L wall-to-lumen ratio; WS, circumferential wall stress, WT, circumferential wall tension; Pre, preintervention; Post, postintervention. reduction in cfPWV has been reported (21,22), yet after 6 mo of exercise training the reduction in cfPWV was not maintained (21). These data suggest that the prescription of aerobic exercise on improving arterial stiffness may be more beneficial before the occurrence of T2DM in those with MetS, than starting once the patient is already at a high cardio-metabolic risk.…”
Section: Controls Metsmentioning
confidence: 84%
See 2 more Smart Citations
“…b, brachial; c, central; SBP, systolic blood pressure; DBP, diastolic blood pressure; PP, pulse pressure; MAP, mean arterial pressure; P1 H, aortic incident pressure wave; AP, aortic augmentation pressure; AGI, aortic augmentation index; AGI@75HR, aortic augmentation adjusted for heart rate; HR, heart rate; SEVR, subendocardial viability ratio; TTI, tension time index; DTI, diastolic time index; AoTr, return of aortic reflective wave; cfPWV, carotid-femoral pulse wave velocity (PWV); crPWV, carotid-redial PWV; Dc, carotid diameter in diastole; CSA, cross-sectional area; CCA, common carotid artery; W/L wall-to-lumen ratio; WS, circumferential wall stress, WT, circumferential wall tension; Pre, preintervention; Post, postintervention. reduction in cfPWV has been reported (21,22), yet after 6 mo of exercise training the reduction in cfPWV was not maintained (21). These data suggest that the prescription of aerobic exercise on improving arterial stiffness may be more beneficial before the occurrence of T2DM in those with MetS, than starting once the patient is already at a high cardio-metabolic risk.…”
Section: Controls Metsmentioning
confidence: 84%
“…Recent evidence suggests that any initial benefit with exercise training on arterial stiffness in persons with established MetS and T2DM is attenuated over the long term (11,21). Whereby at 3 mo of aerobic exercise training a 14 -23% Table 2…”
Section: Relationship Between Aerobic Capacity and Arterial Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that exercise only influenced female measurements, having no effect on male measurements of C-F PWV [12], whereas some have shown a decrease in C-F PWV following exercise in a mixed group [13] and others have found no effect on C-F PWV [14,15]. It is generally well established that a change from a sedentary to an active state improves arterial elasticity [16]; however, short-term improvements in arterial stiffness due to exercise are attenuated over the long term [17]. Further, some of the beneficial changes in arterial stiffness induced by exercise have been associated with loss of fat [18].…”
Section: Table 2 Intersession and Mean Intrasession Coefficient Of Vamentioning
confidence: 99%
“…,標準体重の者に比べて,肥満者の 中心および末梢動脈スティフネスは高いことが明らかに されている [7][8][9] .我々は,これまでに肥満者における食事 改善による減量や定期的な有酸素性運動により,中心動 脈スティフネスは低下することを明らかにした [10][11][12] .ま た,肥満者における定期的な有酸素性運動により,末梢 体力科学 第63巻 第 3 号 333-341 (2014) DOI:10.7600/jspfsm.63.333 膳法(宮木) ,蘇,熊谷,田中,下條,前田 動脈スティフネスは低下することが報告されている 13,14) . 肥満者において過剰に蓄積した脂肪量を減少させるため には,食事コントロールによる摂取エネルギー制限が効 果的であるが,食事改善を行うだけでは,脂肪量ととも に骨格筋量も減少してしまう点が問題視されている.一 方,動脈スティフネスは,持久性能力や骨格筋量に依存 して変化することが示唆されており 15,16)…”
Section: 筑波大学医学医療系,〒305-8574 茨城県つくば市天王台 1-1-(faculty Of Medicine Uniunclassified